(untitled) (Engaged Scholar Journal: Community-Engaged Research, Teaching, and Learning, 2017)
This is a story of crafting a culturally safe learning space in the context of First Nations communities. It is told by two nurse educators working together, one who is Indigenous and one who is not. The word “crafting” is used to describe the collaborative and aesthetic process of co-constructing learning with students, community members and the environment. The relationship between the educational institution and the First Nations communities was guided by the concept of cultural safety. Cultural safety politicizes the notion of culture and disrupts the power imbalance between nurses and the people they work with. A process of collaborative conscientization was used to decolonize our institution and ourselves. This led to new possibilities of crafting an ethical learning space where Eurocentric ideologies could be dislodged from the center in order for Indigenous ways of knowing and learning to emerge. Students experienced a form of relational accountability for their learning through participation in community ceremonies and protocols. What resulted was a unique and transformative learning experience for fourth year Bachelor of Science in Nursing students offered in collaboration between an educational institution and two remote First Nations communities.